Bilateral Symmetrical Herpes Zoster in an Immunocompetent 15-Year-Old Adolescent Boy - Alexander K. C. Leung; Benjamin Barankin (Case Reports in Pediatrics)
Herpes zoster is uncommon in immunocompetent children. The bilateral symmetrical occurrence of herpes zoster lesions is extremely rare. We report a 15-year-old immunocompetent Chinese adolescent boy who developed bilateral symmetrical herpes zoster lesions. To our knowledge, the occurrence of bilateral symmetrical herpes zoster lesions in an immunocompetent individual has not been reported in the pediatric literature.